Preventive health information on the Internet. Qualitative study of consumers' perspectives. - Quintana, Y. (2001)
OBJECTIVE: To explore how best to make high-quality preventive health information available to consumers on the Internet. DESIGN: Focus groups. SETTING: Three urban workplaces and one local hospital with patients from a rural family medical practice. PARTICIPANTS: Twenty-two men and 17 women patients. METHOD: Qualitative survey of four focus groups, analysis of transcripts and researchers' notes. MAIN FINDINGS: Five themes characterized participants' perceptions of a consumer website of evidence-based preventive guidelines: content expectations, website design, trustworthiness of content, marketing, and the implications of consumer health information on the Internet. CONCLUSION: Consumers want preventive health information both for taking care of themselves and for participating in a more informed way in their health care when they see a physician. Findings of this study reveal some ways in which consumers' use of Internet health information can affect physicians' and other health professionals' work.